The hunger games : 4-movie collection [videorecording (Blu-Ray)] - Ross, Gary, 1956-; Lawrence, Jennifer, 1990-; Hutcherson, Josh; Hemsworth, Liam, 1990-; Banks, Elizabeth, 1974-; Harrelson, Woody; Sutherland, Donald, 1935-2024; Hoffman, Philip Seymour, 1967-2014; Moore, Julianne; Collins, Suzanne; Ray, Billy; Beaufoy, Simon; et al. (Lions Gate Entertainment, 2018)
Hunger games: Every year in the ruins of what was once North America, the Capitol of the nation of Panem forces each of its twelve districts to send a teenage boy and girl to compete in the Hunger Games. Sixteen-year-old Katniss Everdeen volunteers in her younger sister's place and must rely upon her sharp instincts when she's pitted against highly trained Tributes who have prepared their entire lives. She must make impossible choices in the arena that weigh survival against humanity and life against love.